Perbandingan Kandungan Lemak, Protein, SNF, dan Berat Jenis Kolostrum Kambing Jawa Randu dan Peranakan Ettawa Di Kabupaten Sumedang (Comparison of Fat, Protein, SNF, and Density of Jawa Randu and Ettawa Crossbreeds Colostrum in Sumedang Regency) - Raden Febrianto Christi; Dwi Suharwanto; Eka Wulandari (Jurnal Sains Peternakan, 2021)
Colostrum is the first liquid that comes out of the teat of dairy cattle. This liquid contains components or compounds that are good for newborn calves including protein, fat, carbohydrates, vitamins and minerals. The purpose of this study was to compare the quality of colostrum content in dairy goats in Sumedang Regency. The research was conducted at the Dairy Goat Farm owned by Mr. Hendar, Pamulihan District, Sumedang Regency, West Java. The research method used a paired t test with 20 head each of the Jawa Randu and Ettawa Crossbreeds of dairy goats at the same birth. Colostrum samples were taken from the morning and afternoon milking, which was 100 ml from each head and then put into a coolbox to test the fat, protein, SNF, and density content in the laboratory. The results showed that of fat, protein, SNF and density content of colostrum in Jawa Randu goats produced a significant effect (P <0.05) compared to colostrum of Ettawa crossbreeds. The conclusion shows that there is a difference between the quality of the colostrum content in Jawa Randu and Ettawa crossbreeds.